1974
DOI: 10.1111/j.1745-6606.1974.tb00878.x
|View full text |Cite
|
Sign up to set email alerts
|

The Grocery Shopper and Food Specials: A Case of Subjective Deception?

Abstract: Advertised food specials may be deceptive to consumers who mistake the advertised prices as reduced prices. Of all the advertised food specials examined in this research, at least 13 percent and as many as 25 percent of those advertised in newspapers were not reduced in price.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

1975
1975
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…Content analyses of Canada Safeway's grocery advertising during the survey period indicate that almost all regularly carried advertised items (97.6 percent) were reduced in price. This finding contrasts sharply to previous analyses reported in Wilkinson and Mason (1974) and Mason and Wilkinson (1976; on grocery advertising in the 1970s by U.S. stores. They found that 25 percent to 48 percent of products featured in national chain grocery advertisements were not actually reduced in price.…”
Section: Discussion and Summarycontrasting
confidence: 99%
See 2 more Smart Citations
“…Content analyses of Canada Safeway's grocery advertising during the survey period indicate that almost all regularly carried advertised items (97.6 percent) were reduced in price. This finding contrasts sharply to previous analyses reported in Wilkinson and Mason (1974) and Mason and Wilkinson (1976; on grocery advertising in the 1970s by U.S. stores. They found that 25 percent to 48 percent of products featured in national chain grocery advertisements were not actually reduced in price.…”
Section: Discussion and Summarycontrasting
confidence: 99%
“…Miscellaneous grocery products included canned and dried fruit, canned vegetables, frozen food, and prepared food. This breakdown of food groups is far more extensive than the three groups (meats, poultry, and fish; fresh fruits and vegetables; and other) used by Wilkinson and Mason (1974). By expanding the number of food groups to ten, consumers can be more articulate as to their perceptions about advertising.…”
Section: Content Analyses Of Advertisements and Comparison To Regularmentioning
confidence: 99%
See 1 more Smart Citation
“…One estimate by the United States Department of Agriculture suggests that consumers can save 10 percent or more on their total food bill by taking advantage of advertised specials in only 2 different supermarkets [19, p. 261. Another study in a Southeastern urban area found that percentage markdowns on advertised food items ranged between 16 and 23 percent for 3 supermarket chains [21]. Clearly, however, many items are advertised without being reduced in price.…”
mentioning
confidence: 99%